Diana Larson and Elaine Mitchell - Unknown:::Creator::::::::::::
Photograph shows Diana Larson (left) and Elaine Mitchell (right) holding a YWCA pamphlet. They are at the 1973 YWCA annual meeting. The pamphlet has a picture of the YWCA building on the cover and the title reads: "Young Women's Christian Association of San Jose."